2012
DOI: 10.4103/2229-5151.100887
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital care of pediatric patients with trauma

Abstract: Prehospital pediatric care is an important component in the treatment of the injured child, as the prehospital responders are the first medical providers performing life saving and directed medical care. Traumatic injuries are the leading cause of morbidity and mortality in the pediatric patient population. Nevertheless, for most prehospital provider it is a rare event to treat pediatric trauma patients and there is a still existing gap between the quality of care for pediatric patients compared to adults. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Fifth, the number of preschool-aged and school-aged children with fatal injuries was lower than that of adults, which may result in a potential source of methodological bias in the assessment. Finally, the study was conducted only in patients admitted in a level I trauma center; whether children received suboptimal prehospital care compared to the adults at a level I trauma center and not at a pediatric trauma center would raise further debate; so the results of this study remained inconclusive [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the number of preschool-aged and school-aged children with fatal injuries was lower than that of adults, which may result in a potential source of methodological bias in the assessment. Finally, the study was conducted only in patients admitted in a level I trauma center; whether children received suboptimal prehospital care compared to the adults at a level I trauma center and not at a pediatric trauma center would raise further debate; so the results of this study remained inconclusive [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…4, 37 These differences may be even more pronounced in children, as severe pediatric trauma is a relatively rare call for GEMS providers. 38 One group found GEMS had unacceptably high complication and failure rates for pediatric intubation, while HEMS crews provided safe and effective intubation. 39 Finally, trauma center access may also play a role in the benefit of HEMS transport.…”
Section: Discussionmentioning
confidence: 99%
“…The physicians who work at SAMU also provide pediatric care and therefore need to master advanced support procedures. One study recommended intensive training for this type of care and reported frequent weaknesses in its implementation ( 34 , 35 ). In the present series, 51.1% of physicians were considered unprepared for pediatric trauma care, 34.9% reported difficulty in assessing pediatric symptomatology, and 62.4% were unprepared for advanced life support procedures.…”
Section: Discussionmentioning
confidence: 99%